2017
DOI: 10.1055/s-0043-110473
|View full text |Cite
|
Sign up to set email alerts
|

The Rotator Interval – A Link Between Anatomy and Ultrasound

Abstract: Shoulder pathologies of the rotator cuff of the shoulder are common in clinical practice. The focus of this pictorial essay is to discuss the anatomical details of the rotator interval of the shoulder, correlate the anatomy with normal ultrasound images and present selected pathologies. We focus on the imaging of the rotator interval that is actually the anterosuperior aspect of the glenohumeral joint capsule that is reinforced externally by the coracohumeral ligament, internally by the superior glenohumeral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The only limiting factor is the presence of acromion, which compromises visualization of underneath soft tissue, for example, RC and RI. 34 Anatomical proximity of the anterior RC and RI presents with "superoanterior lesions." This distinct type of rotator cuff tear involves the subscapularis and anterior portion of the supraspinatus tendon and adjacent RI structures, for example, SGHL, CHL, and biceps tendon.…”
Section: Figmentioning
confidence: 99%
“…The only limiting factor is the presence of acromion, which compromises visualization of underneath soft tissue, for example, RC and RI. 34 Anatomical proximity of the anterior RC and RI presents with "superoanterior lesions." This distinct type of rotator cuff tear involves the subscapularis and anterior portion of the supraspinatus tendon and adjacent RI structures, for example, SGHL, CHL, and biceps tendon.…”
Section: Figmentioning
confidence: 99%
“…Several articles have reported that the morphology of the bicipital groove affects LBT disorders [7][8][9]; some anecdotal studies have not supported any correlation between intra-articular biceps tendon pathology and bicipital groove morphology [10]. Some authors have argued that the transverse ligament does not exist as a separate entity [5,11] but is considered as an extension of the subscapularis tendon and only contributes slightly to the stabilization of the LBT in the bicipital groove [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both run intra‐articularly along the superolateral (lateral band) and inferomedial (medial band) aspects of the long head of biceps tendon. Under tension, the CHL reinforces the glenohumeral joint, especially in external rotation . The RI, which forms in the anterosuperior portion of the glenohumeral joint, is a space created by the coracoid process and the adjacent tendons of the subscapularis and supraspinatus muscle .…”
Section: Introductionmentioning
confidence: 99%
“…Under tension, the CHL reinforces the glenohumeral joint, especially in external rotation . The RI, which forms in the anterosuperior portion of the glenohumeral joint, is a space created by the coracoid process and the adjacent tendons of the subscapularis and supraspinatus muscle . The thickening of the CHL has been linked to GHIAC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation